PENGARUH KEMAMPUAN KERJA, MOTIVASI DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN PT. BINA BUANA SEMESTA - Rosmala Dewi; Meslo Pardede (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2021)
The purpose of this study was to determine the effect of job ability, motivation, and career advancement on the performance of employees of PT. Bina Buana Semesta partially and simultaneously. Causal research methods. The sample in this study was PT. Bina Buana Semesta with 80 respondents. The data used are primary data. The data collection method uses a questionnaire. Analysis of the data used is quantitative using SPSS version 23. The results of this study partially indicate that job ability and career development significantly influence employee performance. While motivation does not significantly influence employee performance.